2008
DOI: 10.1111/j.1365-2052.2008.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for white blood cell numbers in swine

Abstract: Differential white blood cell counts are essential diagnostic parameters in veterinary practice but knowledge on the genetic architecture controlling variability of leucocyte numbers and relationships is sparse, especially in swine. Total leucocyte numbers (Leu) and the differential leucocyte counts, i.e. the fractions of lymphocytes (Lym), polymorphonuclear leucocytes [neutrophils (Neu), eosinophils (Eos) and basophils (Bas)] and monocytes (Mon) were measured in 139 F(2) pigs from a Meishan/Pietrain family, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
5
47
0
Order By: Relevance
“…This region was only identified with CATT, possibly due to its property to detect non-additive effects of the SNP alleles. This region identified on SSC8 harbours several QTL already reported in swine: white blood cell counts (Reiner and others 2007a), bilirubin concentration (Reiner and others 2009), and time spent feeding and lying after infection with S miescheriana (Reiner and others 2007b). This region is surrounded by three genes: SLIT2 ( slit guidance ligand 2), PACRGL (PARK2 co-regulated-like), and KCNIP4 (Kv channel interacting protein 4).…”
Section: Discussionmentioning
confidence: 82%
“…This region was only identified with CATT, possibly due to its property to detect non-additive effects of the SNP alleles. This region identified on SSC8 harbours several QTL already reported in swine: white blood cell counts (Reiner and others 2007a), bilirubin concentration (Reiner and others 2009), and time spent feeding and lying after infection with S miescheriana (Reiner and others 2007b). This region is surrounded by three genes: SLIT2 ( slit guidance ligand 2), PACRGL (PARK2 co-regulated-like), and KCNIP4 (Kv channel interacting protein 4).…”
Section: Discussionmentioning
confidence: 82%
“…We detected a neutrophil QTL at 106 Mb on the same chromosome (Table 3). For the same trait, Reiner et al (2008) reported two QTL in a Meishan×Pietrain cross, which were located at 8 cM on SSC4 and at 23 cM on SSC11, respectively. In the similar regions, two QTL were detected at 17 Mb and 18 Mb in the respective chromosomes (Table 3).…”
Section: Resultsmentioning
confidence: 96%
“…We should note that many QTL mapping designs used families that were developed by crossing European Wild Boar with a commercial breed or crossing the Chinese Meishan breed with a commercial breed (Rothschild et al, 2007). For example, an overlap could be formed by a growth-related QTL identified in a family generated by cross-breeding of Duroc and Pietrain (Liu et al, 2007) and an immunity-related QTL in a family generated by cross-breeding of Pietrain and Meishan (Reiner et al, 2008). Therefore, to decrease false-positive findings, we set the threshold to be a conservative value -10 kb.…”
Section: Pleiotropy Of Growth and Immunity On Meishan Pigsmentioning
confidence: 99%